Sex and gender in perioperative cardiovascular research: protocol for a scoping review - Ana Sjaus; Nicole Fakhory (Systematic Reviews)
Abstract Background The inadequate inclusion of sex and gender in medical research has resulted in biased clinical guidance and disparities in knowledge and patient outcomes. Despite efforts by regulatory and funding agencies, opportunities to generate sex-specific knowledge are frequently overlooked. While certain disciplines in cardiovascular medicine have made notable progress, these advances have yet to permeate the literature on perioperative cardiovascular complications in non-cardiac surgery. Prompted by the recent findings on sex-specific perioperative cardiovascular outcomes, this review aims to scope the literature in this field and categorize methodological approaches used to incorporate sex and gender in studies of this patient population. Methods Joanna Briggs Institute (JBI) methodology for scoping reviews will be followed in stages elaborated by Levac (2010). A comprehensive search strategy will be used to identify relevant primary research published since 2010. Screening will be performed by independent reviewers using predefined inclusion and exclusion criteria. Data will be extracted from full text and supplementary materials of selected articles. Results will be presented as proportions of studies reporting sex and gender, the assigned purpose of these variables in analysis, and where they are reported in the article. In addition, articles will be mapped to the source, country of origin, and year of publication. Narrative summaries will be provided to outline key findings and assess the depth of the literature within each of the major topics (risk assessment/prediction, diagnosis, treatment, prognosis, and outcomes). Discussion Increasing recognition of the profound and complex implications of sex and gender in medicine has fuelled calls for greater attention to participation equity, sex-specific analysis and reporting. Focusing on perioperative cardiovascular complications, this review has the potential to identify knowledge gaps for future research, as well as areas of strength that could support formal knowledge synthesis or secondary analysis of data from past research. Scoping review registration Submitted on August 15th, 2023 (Web of Science osf.io/u25sf)